NIH roadmap for medical research and knowledge-based economy - Iraj Nabipour (Iranian South Medical Journal, 2012)
Although knowledge has long been an important factor in economic growth, economists are now exploring ways to incorporate more directly knowledge and technology in their theories and models. “New growth theory” reflects the attempt to understand the role of knowledge and technology in driving productivity and economic growth. The NIH Roadmap for Medical Research was launched in September, 2004, to address roadblocks to research and to transform the way biomedical research is conducted by overcoming specific hurdles or filling defined knowledge gaps. Roadmap programs span all areas of health and disease research and boundaries of NIH Institutes and Centers (ICs). These are programs that might not otherwise be supported by the NIH ICs because of their scope or because they are inherently risky. Roadmap Programs are expected to have exceptionally high potential to transform the manner in which biomedical research is conducted. They are also expected to be short term, 5–10 year programs. This book presents the major areas of medical research which were emphasized in the NIH Roadmap for Medical Research. The step by step engagement of this roadmap in knowledge-based economy would be elucidated in this review.